Current management of shoulder adhesive capsulitis: a randomized, triple-blind placebo-controlled trial - Almashni, Riyadh A.; Calacattawi, Abdullah W.; Almeshal, Meshal A.; Alsharif, Elaf J.; Hijazi, Mohamad W.; Abdulwahab, Shahd A.; Alsharif, Anfal J.; Altufayl, Nasser O.; Alghamdi, Anwar A.; Almuzayyen, Hisham A. (International Journal Of Community Medicine And Public Health, 2018)
This review is aiming to discuss both operative and non-operative current management of this adhesive capsulitis. The present review was conducted in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) declaration standards for systematic reviews. A systematic search for the terms adhesive capsulitis, frozen shoulder, glucocorticoid, non-operative operative, current management, and management of systematic review in different databases, including MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials (CENTRAL), were searched up to March 2018 for published and unpublished studies and without language restrictions. The majority of the trials show level 2 [mid-level] evidence, positive results were found for intra-articular corticosteroid injections combined with shoulder mobility and stretching exercises are more eﬀective in providing short-term (4-6 weeks) pain relief and improved function compared to shoulder mobility and stretching exercises alone. On the basis of current clinical evidence, this systematic review suggests that there is no strong evidence to support or refute the current practice in term of adhesive capsulitis management. As there is a need of further research in this issue and to have clear uniformed prospective about the adhesive capsulitis.